2000
DOI: 10.1007/s001340051208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothermia on ventilation in anesthetized, spontaneously breathing rats: theoretical implications for mechanical ventilation

Abstract: Mild hypothermia in rats, induced by a sustained pentobarbital anesthesia, reduces ventilation without compromising arterial oxygenation or acid-base balance, as measured at body temperature. Theoretically, our observations in spontaneously breathing rats imply that a combination of mild hypothermia with anesthesia could be safely utilized to maintain adequate ventilation, using relatively low minute ventilation. We speculate that such a maneuver, if applied during mechanical ventilation, may prevent secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the hypothermic cohort, the heart rate was around 15% lower, a physiological response to this condition ( Fig. 1D; Sabharwal et al, 2004;Torbati et al, 2000). Physiological measures otherwise demonstrated no significant differences in the parameters measured throughout the 8-h period (Table 2).…”
Section: Physiological Monitoringmentioning
confidence: 79%
“…In the hypothermic cohort, the heart rate was around 15% lower, a physiological response to this condition ( Fig. 1D; Sabharwal et al, 2004;Torbati et al, 2000). Physiological measures otherwise demonstrated no significant differences in the parameters measured throughout the 8-h period (Table 2).…”
Section: Physiological Monitoringmentioning
confidence: 79%
“…Data on animals show a reduction of MV after induced MH probably due to a reduction of the respiratory effort 3 4. Our patients did not change MV and TV if different core temperatures were achieved, even if a slight not statistically significant difference in MV, higher in the DH group, was recorded.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, despite the increase in RR upon rewarming to normothermia, Vt remained unexpectedly high in certain types of breaths. During the rewarming process, there is a significant increase in carbon dioxide blood levels due to increased metabolic demands, oxygen consumption, and carbon dioxide production ( 39 ). Previous experiments conducted by Torbati et al on anesthetized spontaneously breathing rats, the authors observed a Vt of 7.6 ± 3.1 ml/kg before hypothermia and 10.3 ± 4.2 ml/kg after rewarming ( 39 ).…”
Section: Discussionmentioning
confidence: 99%